'Working on Holiday': Relationships between Tourism and Work among Young Canadians in Edinburgh. (2010) - ,
Abstract : Working holiday-maker programmes have facilitated a growing cohort of mobile young people who have an ambiguous status as both worker and tourist. Drawing on ethnographic fieldwork conducted among Canadian working holiday-makers in Scotland, this paper shows how working holiday-makers are situated in an ambiguous, contradictory position as working tourists, and are streamlined towards particular social and professional fields in which work-leisure boundaries are blurred. Although these blurred boundaries seem contradictory, they benefit employers who require an educated yet temporary work-force, while also meeting the desires of working holiday-makers for a lifestyle that is flexible, social, far from the pressures of friends and family, and that puts them in regular contact with other young foreigners who, like them, are at transitional points in life.